Sustainability of Coffee Farming with the Application of Biopesticides of Angel’s Trumpet White Flower (Brugmansia Suaveolens Bercht. & J. Presl) and Mahogany Leaves (Swietenia macrophylla) - Dedi Arta Putra; Aminudin Afandhi; Rita Parmawati (Postgraduate, University of Mataram, 2025)
This study examines the sustainability of coffee farming in Ledug Village, Prigen, through the application of natural biopesticides derived from mountain brugmansia flowers (Brugmansia suaveolens) and mahogany leaves (Swietenia macrophylla). The research evaluates sustainability across five key dimensions: ecological, economic, social, technological, and institutional. Using Multi-Dimensional Scaling (MDS) Rapfish, SWOT, and QSPM methods, the findings reveal that the ecological dimension achieved a sustainability index of 76.41%, indicating a moderately sustainable status, with the use of chemical fertilizers identified as a critical sensitive factor. The economic dimension scored 65.48%, with market competitiveness and long-term profitability as main drivers. The social dimension reached 68.79%, influenced by farmer education, training, and overall well-being. Technological sustainability was measured at 62.74%, highlighting the importance of innovation and access to farming technology. Institutional sustainability was supported by mentoring programs with a high leverage score. Based on SWOT analysis, the WO strategy was prioritized to improve sustainability by enhancing partnerships, expanding market access, and fostering innovation. QSPM analysis emphasized two strategic actions: promoting eco-friendly coffee products using natural biopesticides and collaborating with NGOs to implement environmentally sustainable technologies. Recommendations include reducing chemical inputs, strengthening institutional support, and increasing farmer capacity through training.